Histomorphology of bone marrow from adult pancytopenic patients at the University Teaching Hospital in Lusaka, Zambia - Musonda, Francis; Marimo, Clemence; Kowa, Sumbukeni (Medical Journal of Zambia, 2019)
Background: Pancytopenia is a haematologic condition characterised by leukopenia, anaemia and thrombocytopenia. Pancytopenia is not a diagnosis and has to be qualified by determination of its cause. The aetiologies of pancytopenia are diverse, and study of bone marrow histomorphology via cytology and histology are key components that assist in the determination of the underlying cause. Pancytopenia is encountered regularly in medical practice in Zambia, however, no studies have been conducted on pancytopenia to date. This was a descriptive cross-sectional study done on adult pancytopenic patients admitted to the medical wards of the University Teaching Hospital (UTH) over an eight-month period. The aim of this study was to determine the histomorphology of the bone marrows of adult pancytopenic patients admitted to the UTH.Methods: A total of 45 bone marrow biopsies were collected over the study period. In all cases the indication was pancytopenia that had been confirmed by a full blood count done at the UTH and the biopsy site was either the anterior superior iliac spine or the posterior superior iliac spine. Demographic and clinical details were obtained using data collection sheets and from review of patient records. The collected data was analysed using the Statistical Package for the Social Sciences (SPSS) version 21. A Chi square test was used to measure association between categorical variables. A p value of < 0.05 at 95% confidence interval was considered statistically significant.Results: There were 32 females (71%) and 13 males (29%), and the age ranged from 15 to 72 years with an average age of 35 years. Forty percent (n=18) of t h e study participants had human immunodeficiency virus (HIV) and all of these all were on highly active antiretroviral therapy (HAART). There were 6 histologic patterns found the commonest being megaloblastosis seen in 38% of the patients, followed by malignancy and myelodysplasia both at 17.0%. Bone marrow aplasia accounted for 13.0%, non-megaloblastic erythroid hyperplasia accounted for nine percent and myelofibrosis for four percent. A chi square test was used to determine if there was association between each histomorphology and HIV status, the only significant result was obtained from the Chi test applied to HIV status and myelodysplasia which gave a p value of 0.026. The Chi square test involving the other histomorphologies all yielded a p value greater than 0.05.Conclusion: The bone marrow biopsies of the study population showed six histomorphologic pictures which in order of frequency were megaloblastosis, malignancy and myelodysplasia, bone marrow hypoplasia, non-megaloblastic erythroid  hyperplasia and myelofibrosis. Association was found between HIV status and myelodysplasia via the Chi square test.
Keywords: Pancytopenia; Bone marrow; Trephine and Histomorphology